The motivation of undergradutes learning Mandarin as a foreign language / Teow Ghee Tan ... [et al.] - Ghee Tan, Teow; Ismail, Hairul Nizam; Terng Hoe, Foo; Chui Ho, Chui (2016)
Motivation has been defined as the learner's orientation with regard to the learning goals of a second or foreign language. Scholars and researchers believe that second or foreign language learners will devote considerable effort to achieve their learning goals. Learning goals are essential for learning a second or foreign language successfully. Thus, this study applied a qualitative research design which emphasized data collection from educational artefacts. Convenience sampling method was used for collecting data. Essays written by 65 students providing their goals for learning Mandarin from a university which only caters for indigenous students were collected and analysed. All the essay writers were students who were enrolled in a Mandarin course in three different levels. All of them were aged 21-22 with an average age of 21.7. Content analysis was employed to explore information from the transcripts. Thirty themes of learning goals were found from the data which were subsequently grouped into nine motivational categories: Future Career, Communication, Future Self, Interest, Friendship, External Influence, Culture, Academic Requirement, and Travel. The study recommends curricula planners to strengthen the present curriculum for the Mandarin courses with the students' learning motivations as one of the ways to encourage learners to devote more efforts to their language learning. The study also suggests that for the future, similar studies should be replicated with a blended motivational framework and a triangulation method designed to find support for the findings of this study as well as to explore more fully the relationships among various types of motivations.